PENGEMBANGAN BAHAN AJAR BERBASIS MODEL PEMBELAJARAN DISCOVERY LEARNING DI SD/MI - Syahidan Nurdin; Nurliani Anjani Cibro; Wati Oviana (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2023)
Lack of learning resources is an obstacle in achieving curriculum goals. The diversity of learning resources, especially teaching materials, is still lacking in primary schools and madrasah. It is important to develop teaching materials that are in accordance with the theme of the curriculum in Primary school. This study aims to design teaching materials based on the discovery learning model and describe the feasibility of teaching materials based on the discovery learning model in class IV primary school. This study uses Research and Development (R&D) research using the 4D model which consists of 4 stages, namely: Define Design, Develop and Dissemination. The research instruments were media expert validation sheets, material expert validation sheets, linguist validation sheets and teacher response questionnaires. Based on the results of this study, it shows that the media validation results obtained a score of 94% in the very feasible category, the results of the material expert validation obtained a score of 80% in the feasible category, the results of the linguist validation obtained a score of 82% in the very feasible category, and the results of the first teacher's response scored with the percentage is 80% in the appropriate category, the results of the second teacher's response obtain a score with a percentage of 81% in the very feasible category. Based on the results of these data, it can be concluded that the development of teaching materials based on the discovery learning model is suitable for use for fourth grade students of Primary school.